2022
DOI: 10.1038/s41467-022-33109-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale RNA interference profiling of Trypanosoma brucei cell cycle progression defects

Abstract: Trypanosomatids, which include major pathogens of humans and livestock, are flagellated protozoa for which cell cycle controls and the underlying mechanisms are not completely understood. Here, we describe a genome-wide RNA-interference library screen for cell cycle defects in Trypanosoma brucei. We induced massive parallel knockdown, sorted the perturbed population using high-throughput flow cytometry, deep-sequenced RNAi-targets from each stage and digitally reconstructed cell cycle profiles at a genomic sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 117 publications
1
17
0
Order By: Relevance
“…Yet, in BSFs CYC9 transcript depletion results in a clear cytokinesis defeat 82 . Thus, transcript FC does not necessarily correlate with functional significance, as was also noted when comparing CCR genes to cell cycle defects profiled by the genome-scale screen in BSFs 45 . Results of CYC9 RNAi depletion in PCFs is currently conflicting, possibly due to differences in knockdown efficiency, as one study observed a substantial cell cycle arrest in G2/M 77 , while another saw no specific arrest in any cell cycle phase 82 .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Yet, in BSFs CYC9 transcript depletion results in a clear cytokinesis defeat 82 . Thus, transcript FC does not necessarily correlate with functional significance, as was also noted when comparing CCR genes to cell cycle defects profiled by the genome-scale screen in BSFs 45 . Results of CYC9 RNAi depletion in PCFs is currently conflicting, possibly due to differences in knockdown efficiency, as one study observed a substantial cell cycle arrest in G2/M 77 , while another saw no specific arrest in any cell cycle phase 82 .…”
Section: Discussionmentioning
confidence: 91%
“…The additional CCR genes identified only in BSF included those linked to glycolysis, which BSFs rely on to generate ATP from the glucose energy source in the mammal 63 . Interesting, the knockdown of 11 glycolysis-associated genes was linked to cell cycle arrest in G1 45 and so further investigation may unveil if BSFs use glycolysis activity levels as a signal for re-entering the cell cycle during G1. Other genes uniquely CCR in BSFs include DNA recombination factors, RecQ helicase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4) for association with the flagellar axoneme or the flagellum, suggesting an important impact of cAMP signalling on flagellar biology. An intact and functional flagellum was previously shown to be essential for cell division of bloodstream stage trypanosomes, as RNAi repression of many genes with flagellar localization or function result in a lethal cell division phenotype (Broadhead et al ., 2006; Marquez et al, 2022). This may explain why the screen returned specifically the observed set of proteins.…”
Section: Discussionmentioning
confidence: 99%